Principle of Non-discrimination and Equal Treatment - Moroşteş, Anca; Stoicu, Narcisa Mihaela (Journal of Legal Studies, 2021)
With its evolution, society has introduced human rights as intrinsic values in its acts on the regulation of relations of human nature. Significant victories in the struggle for social freedoms materialized with the adoption of the first declarations of rights, which formed the basis for the passing of later constitutions. Therefore, the modern state, inclined to the protection of its citizens, is unthinkable in its functionality, without stating and guaranteeing human rights in their fundamental law. In addition, it is necessary to point out that these rights have a universal character, namely their protection for each person, regardless of nationality, ethnicity, race, religion, level of health, person’s status, etc. The Constitution of Romania states in art. 15 par. (1) on this that: "All citizens benefit from the rights and freedoms enshrined in the Constitution and other laws and have the obligations provided for therein".